Physics for game programmers. - Palmer, Grant, ....- (Berkeley : Apress, 2005)
First, you can get the source code directly from Apress' website. Second...the implementations are in simple terms. Third...(Grant Palmer's) book is full of trivia about physics that are just plain fun to read. - InkBlog: The Random Musings of David Weller As far as the style of the book goes, I think that's actually where it really shines. The author has a way of explaining things that's thorough without being verbose. - Craig Andera, Pluralsight "Physics for Game Programmers" shows you how to infuse compelling and realistic action into game programming--even if you don't have a college-level physics background! Author Grant Palmer covers basic physics and mathematical models and then shows how to implement them, to simulate motion and behavior of cars, planes, projectiles, rockets, and boats. This book is neither code heavy nor language specific, and all chapters include unique, challenging exercises for you to solve. This unique book also includes historical footnotes and interesting trivia. You'll enjoy the conversational tone, and rest assured: all physics jargon will be properly explained.
Keywords: Computerspelen; Fysica